Analisis Pemeliharaan Mesin Extrusion Press Pada Produksi Ban Dengan Menggunakan Penerapan Total Productive Manitenance (TPM) di PT. XYZ - Faza Roshandika Pratama; Wahyudin Wahyudin (Jurnal Serambi Engineering, 2023)
PT. XYZ is a company that produces motorcycle and car tires. This company has a fairly broad product market, so the products it manufactures have good product quality. In producing tires, one of the machines used in producing tires is an extrusion press machine. In carrying out its production, the extrusion press experiences downtime in the period August-December 2022, where the biggest downtime occurs in August, which has a downtime of 1890 minutes. After conducting an analysis using the Overall Equipment Effectiveness method to determine the level of effectiveness of the extrusion press machine, the OEE value calculation results from the August-December 2022 range are less than the international standard value of 85%. so we need an increase in the OEE value on the extrusion press machine. In increasing the OEE value, better engine maintenance is needed, so the Total Productive Maintenance (TPM) method is used as an effort to make engine maintenance even more effective.